MICROWAVE TRAVELLING WAVE TUBE - A SUMMARY OF AN ANALYTICAL, NUMERICAL AND EXPERIMENTAL THERMAL ANALYSIS - Wymysłowski, Artur; Wiejak, Waldemar; Słupski, Piotr (International Journal of Research -GRANTHAALAYAH, 2017)
Travelling Wave Tube (TWT) is an electronic vacuum microwave device, which is used as a high power microwave amplifier, mainly in telecommunication purposes and radar systems. TWT's seem to be an alternative and a more reliable solution than semiconductor devices when building high power and high frequency applications. Thermal behaviour of TWT is one of the key aspects influencing its reliability and working parameters. In fact, the standard TWT is treated as a high power device and the supplied power is dissipated mainly through conduction and convection phenomena. In practical applications, depending on a type of TWT, they can be cooled either by a forced liquid or air circulation. The main goal of the presented research was to perform analytical, experimental and numerical analysis of temperature distribution of a low band TWT in case of a typical working condition. Because theoretical analysis seems to be very complex, thus it was decided to support it with experimental measurements and numerical simulations as well as with the simplified analytical formulas. As a first step of the presented research, the analytical analysis and numerical modelling of the helix TWT was carried out. The objective of the thermal analysis was to assess the temperature distribution in different parts of the helix TWT assembly during extreme standard and working conditions. Afterwards, the obtained numerical results were validated by experimental measurements, which were carried out using a custom designed TWT test sample and corresponding experimental measurement tools.